Paul on identity : theology as politics - Engberg-Pedersen, Troels (Fortress Press, 2021)
One of the most important and controversial questions in biblical studies is how Paul's view of the fundamental Christ identity relates to other possible identities in the Greco-Roman world--like being a Jew or a non-Jew, a man or a woman, a master or a slave. Paul on Identity explores these issues and, in particular, how Paul's view informs his writing. Engberg-Pedersen keeps an eye on what we may or may not accept from Paul and concludes by showing Paul's direct relevance to identity politics.